RUSSIAN INDUSTRY INVESTMENT SITUATION - O. V. Pochukaeva; T. G. Orlova (Модернизация, инновация, развитие)
The actual deficiency of investment into Russian industry innovative development increases its technological drag from industries of countries with developed markets. Although the rate of investment into real sectors of Russian economics mid 2000 was higher compared to the previous period, annual investment amounts were much lower than in 1990. At present, highest investment amounts are directed to industry extractive branches and to the commerce. Amounts invested to various economy branches do not correspond to their contribution to the country’sGross Added Product; particularly underinvested are manufacturing industry branches. At present, foreign share in the country economy total investment makes 15–18%. Recently, most interesting for foreigners was investment to machine-building branches with overwhelming part (for example, 90% in 2007–2008) of foreign investment into the machine-building industry being directed to creation of new automobile plants. Today, first place in the list of foreign investors’ preferences in Russia is taken by the machine-tool construction sector.